Governance Networks in Urban Tourism Policy - Halilm, Hilman Abdul; Nurasa, Heru; Rusli, Budiman; Sugandi, Yogi Suprayogi (Universitas Padjadjaran, 2024)
Tourism Village governance networks are something that is still relatively unfamiliar to be developed in urban tourism. This research aims to analyze the principles of governance networks in the Bandung City Tourism Village (Braga Creative Tourism Village). The research was conducted using qualitative descriptive methods. Data was obtained through observation, interviews, and document studies with the stakeholders involved. The results of the research show that of the four dimensions of governance networks, there is one dimension that is working well, namely formation, while the three dimensions, namely operations, performance accountability, and desire, are not yet working well. The findings in this research are that the state needs to have a greater role than other actors because society's capacity is still small in the economic aspect and there is a link between the success of governance networks and the maturity of democracy in a country, so that the more mature a level of democracy, the greater the level of governance networks success obtained.